Projeto auxiliado por computador de processos industriais sustentáveis e seguros usando simulador de processos - Gonçalves, Ricardo Vieira (2015)
Risk analysis procedures are common in industrial processes, but applied in the final stages of plant design process. When risk assessment procedures are applied in early stages, better results are obtained. In this work an optimization procedure applied to risk analysis was used in order to estimate the total cost of a process (Ctotal) as a function of cost of equipaments (Ceqq) and cost of accidents (Cacc). The cost of accidents was obtained evaluating the potential risks present in a plant and the consequences of an accident, if it occurs, can cause to people, the environment, equipment, etc. Since the relationship between the cost of investment in equipment and cost of accidents is indirect, an optimization procedure may be applied to obtain a \ optimal scenario ". For evaluating the optimization methodology applied to risk analysis, was used the biodiesel production plant for case study. Several literature studies simulate, evaluate and optimize the production of biodiesel plant, though these studies are done only in the technological and economic context, any assessment that addresses risk analysis procedures in the early stages was applied. For construction, simulation and evaluation of the biodiesel production process was used the software COCO, a free software supporting the CAPE-OPEN protocol and that contain more than 400 compounds in its database (PCDmanager), however, not all substances present in the biodiesel production process are present in the database, making necessary insert them. For the insertion of the missing substances, it was created an algorithm in Scilab containing various correlations and group contribution methods (J oback, Constantinou and Gani, Marrero and Gani, etc.) able to predict the thermo-physical properties of pure compounds. Once these properties have been predicted, the inclusion of the missing substances was made in the PCDmanager. The process simulated in software COCO presented results near to the literature, 95% of conversion in the transesterification reactor and a biodiesel product stream 1066.75 kg/h, with a purity of 92%. The optimization procedure applied to risk analysis concluded that the number of methanol storage tanks in the biodiesel production process should be equal three, thus yielding the lowest total cost.